Meckel Syndrome: A Clinical and Molecular Overview - Valentini, Giulia; Saia, Maria; Farello, Giovanni; Salpietro, Vincenzo; Mancuso, Alessio; Ceravolo, Ida; Colucci, Pia V.; Torre, Manuela; Iapadre, Giulia; Rosa, Gabriella Di; Cucinotta, Francesca (Journal of Pediatric Neurology, 2022)
Meckel syndrome (MKS) is a lethal, autosomal recessive, congenital syndrome caused by mutations in genes that encode proteins structurally or functionally related to the primary cilium. MKS is a malformative syndrome, most commonly characterized by occipital meningoencephalocele, polycystic kidney disease, liver fibrosis, and post- and (occasionally) preaxial polydactyly. To date, more than 10 genes are known to constitute the molecular background of MKS, displaying genetic heterogeneity. Individuals with MKS may resemble some phenotypic features of Joubert syndrome and related disorders, thus making diagnostic setting quite challenging. Here, we systematically reviewed the main clinical and genetic characteristics of MKS and its role among ciliopathies.
Keywords: Meckel syndrome; MKS; ciliopathy; meningoencephalocele; oligohydramnios